2021
DOI: 10.1515/nanoph-2020-0647
|View full text |Cite
|
Sign up to set email alerts
|

Nanoscale structural characterization of plasmon-driven reactions

Abstract: Illumination of noble metal nanostructures by electromagnetic radiation induces coherent oscillations of conductive electrons on their surfaces. These coherent oscillations of electrons, also known as localized surface plasmon resonances (LSPR), are the underlying physical cause of the electromagnetic enhancement of Raman scattering from analytes located in a close proximity to the metal surface. This physical phenomenon is broadly known as surface-enhanced Raman scattering (SERS). LSPR can decay via direct in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 118 publications
0
18
0
Order By: Relevance
“…The yield and selectivity of Al- and Cu-based catalysts can be improved via a detailed understanding of photocatalytic processes at the nanoscale . Tip-enhanced Raman spectroscopy (TERS) is an innovative optical nanoscopy technique that can be used to examine the structure of biological specimens, polymers, and chemical and catalytic processes. In TERS, plasmonic nanostructures are created by a metal evaporation or an electrochemical etching at the apex of the scanning probe. , If such a probe is positioned above the sample and illuminated by light, LSPRs at its apex will enhance the Raman scattering from analytes located directly under the probe. The metalized scanning probe is then rastered above the surface of the sample of interest with a simultaneous acquisition of TERS spectra. Next, the spectra are used to generate a chemical map that reveals the structure and composition of the analyzed specimen with a sub-nanometer spatial resolution. …”
mentioning
confidence: 99%
“…The yield and selectivity of Al- and Cu-based catalysts can be improved via a detailed understanding of photocatalytic processes at the nanoscale . Tip-enhanced Raman spectroscopy (TERS) is an innovative optical nanoscopy technique that can be used to examine the structure of biological specimens, polymers, and chemical and catalytic processes. In TERS, plasmonic nanostructures are created by a metal evaporation or an electrochemical etching at the apex of the scanning probe. , If such a probe is positioned above the sample and illuminated by light, LSPRs at its apex will enhance the Raman scattering from analytes located directly under the probe. The metalized scanning probe is then rastered above the surface of the sample of interest with a simultaneous acquisition of TERS spectra. Next, the spectra are used to generate a chemical map that reveals the structure and composition of the analyzed specimen with a sub-nanometer spatial resolution. …”
mentioning
confidence: 99%
“…Also, plasmon-driven catalytic reaction of 4-ATP to 4,4′- dimercaptoazobenzene (DMAB) can be clearly identified by the Raman signatures at 1141 cm –1 due to δ­(CH) and 1392, 1438 cm –1 due to ν­( N  N ) . This surface-catalyzed reaction has demonstrated the hot-electron generation on the AuNPHs plasmonic sheet and in turns proves its SERS efficiency. , Strikingly, the characteristic peak of 4-ATP can be even detected when the concentration was reduced to nanomolar scale. Therefore, it was demonstrated that the detection limit of the plasmonic AuNPH nanosheeta can reach to 10 nM.…”
Section: Results and Discussionmentioning
confidence: 94%
“…54 This surfacecatalyzed reaction has demonstrated the hot-electron generation on the AuNPHs plasmonic sheet and in turns proves its SERS efficiency. 55,56 Strikingly, the characteristic peak of 4-ATP can be even detected when the concentration was reduced to nanomolar scale. Therefore, it was demonstrated that the detection limit of the plasmonic AuNPH nanosheeta can reach to 10 nM.…”
Section: Resultsmentioning
confidence: 99%
“…Chemical transformations of various chemical species on the surfaces of plasmonic metal nanostructures (NS) have recently become a subject of focused interest particularly in connection with identification of plasmon-catalyzed reactions and elucidation of their mechanisms. [1][2][3][4][5][6][7][8][9][10][11][12][13] Plasmon catalysis provides challenging possibilities of conversion of light energy into chemical bond energy. [1][2][3][4][5][6][7][8][9][10][11][12][13] Surface-enhanced (resonance) Raman spectroscopy (SERS and SERRS) has been established as the most suitable tool for monitoring reactions of molecular species in hybrid systems with plasmonic NS, such as Ag and Au nanoparticles (NPs).…”
Section: Introductionmentioning
confidence: 99%